Efeito da ultramaratona 24h sobre biomarcadores de inflamação e dano tecidual em atletas de elite e amadores - REZENDE, Fernando Nazário de (2013)
Introduction: Racing ultraendurance may cause several problems on physiological systems, including alterations in cardiac and inflammatory biomarkers, tissue damage and sudden death. The aim of this study was to assess the effect of race ultraendurance 24 hours in response of biomarkers of inflammation and tissue injury in runners and Elite Amateurs. Methods: The biomarkers: Total creatine kinase (CK), CK MB fraction, Pro-BNP, troponin T, C-reactive protein (CRP), fibrinogen, creatinine, urea, TGO-AST, TGP-ALT and cortisol were assessed before and after 24 h race in 3 groups: Elite Athletes (EA; 11 men, 41.3±9.1 yrs, 74±9.4 kg, 174.3±6.4 cm; ultra-endurance practice time 4.3±4 yrs), amateur athletes men (AAM; 14 men, 43.1±8.7 yrs, 75.7±9.4 kg, 173.5±5.5 cm; ultra-endurance practice time 4.5±5.8 yrs) and amateur athletes women (AAW; 10 women, 50.7±10.7 yrs, 58.4±8.2 kg, 157.5±6.1 cm; ultra-endurance practice time: 7.4±2.2 yrs. Blood samples were collected 1 hour before and immediately after the race. A P<0.05 was considered significant. Results: After 24-hour race, the distance traveled by the groups was different (in km, EA: 158.7±15.7, AAM: 116.7±10.1, AAW: 101.9±18.2; P<0.05). Comparing biomarkers post-race: Total CK (EA: 7388.6± 6484.2 UL; AAM: 2895.9±3199 UL; AAW: 2499±3879 UL), CK-MB fraction (EA: 100.2±76.3 mg/ml; AAM: 28.3±32.6 mg/ml; AAW: 43.4±70.4 mg/ml), Pro-BNP (EA: 532.9±314.6pg/ml; AAM: 220.4±237.8 pg/ml; AAW: 396.5±293.9 pg/ml), troponin T (EA: 0.012 ng/ml; AAM: 0.005±0.002 ng/ml; AAW: 0.0124 ng/ml), C-reactive protein (EA: 0.10±0.10 ng/dl; AAM: 0.06±0.05 ng/dl; AAW: 1.84±1.0 dg/ml), fibrinogen (EA: 338±60 mg/dl; AAM: 347±66.2 mg/dl; AAW: 325±58.1 mg/dl), creatinine (EA: 1.01±0.3 mg/dl; AAM: 0.86±0.3 mg/dl; AAW: 0.86±0.2 mg/dl), Urea (EA: 57±20.9 ng/dl; AAM: 41.5±11 ng/dl; AAW: 47.4±9.7 ng/dl) TGO-AST (EA: 209.8±151.4U/L; AAM: 101.3±117 U/L; AAW: 99.2±143.5 U/L), TGP-ALT (EA: 32.9±18.6 U/L; AAM: 19.7±17.6 U/L; AAW: 20.9±20.5 U/L) and cortisol (EA: 23.34±11.4μ/dl; AAM: 13.85± 8.72 μ/dl; AAW: 16.33±7.4 μ/dl). Discussion The main finding of the study was the increasing amounts of the biomarkers to extremely high values. AAW group showed larger increases than AAM, despite having traveled a smaller distance. However, EA group showed significantly higher values than others. This response may be related to greater distance traveled and relative intensity during the race compared to AAM and AAW groups. The change percentage of biomarkers was significantly different after race in all groups.